Pemberontakan Petani Banten 1888: Narasi Sejarah Sartono Kartodirdjo tentang Perempuan - Ramona, Elza; Angraini, Peppy (Jurnal Sejarah Indonesia, 2025)
This article aims to analyze women narrated by Sartono Kartodirdjo in his work on the figure of Queen Siti Aminah. This article is a historical research with a feminist approach. Data collection was carried out by tracing sources, whether in the form of books, journal articles, or online media searches related to Sartono Kartodirdjo, portraits of women in historical writing, and things related to the research theme. Through his monumental work, Pemberontakan Petani Banten 1888, Sartono presents Queen Siti Aminah in a special discussion. Queen Siti Aminah is described as a tough woman. With the capacity and privilege she has, she can rebuild trust in the Kesunyatan Banten family and defend her religion, Islam.